Douglas H. Johnson: Nuer Prophets. A history of Prophecy from the Upper Nile in the Nineteenth and Twentieth Centuries - Johnsen, Nina (Tidsskriftet Antropologi, 2019)
Douglas H. Johnson: Nuer Prophets. A history of Prophecy from the Upper Nile in the Nineteenth and Twentieth Centuries Anmeldes af Nina Johnsen